La Colonia Digital Archive: New Haven's Italian American Community, 1890–1930 - Larkin, Erin (2026)
La Colonia Digital Archive: New Haven's Italian American Community, 1890–1930 is an open-access digital humanities project documenting the professional and civic life of New Haven's Italian American community between 1890 and 1930. The archive is based on Antonio Cannelli's La Colonia Italiana di New Haven (1921), a 373-page Italian-language volume combining a community Who's Who with a survival guide for new immigrants. Cannelli documented 248 individuals and more than 90 businesses, including physicians, attorneys, pharmacists, musicians, grocers, and bankers. Cannelli published his volume in 1921, the same year that Nicola Sacco and Bartolomeo Vanzetti went on trial for murder in Massachusetts; they were convicted on July 14, 1921, and sentenced to death in a case that became an international cause célèbre and a defining watershed of anti-immigrant sentiment directed specifically at Italians. The trial unfolded against a broader landscape of systematic exclusion: the Emergency Quota Act of 1921 had passed just months earlier, sharply restricting Southern and Eastern European immigration, and Italians faced sustained targeting, marginalization, and persistent characterization as unskilled, unassimilable, and threatening. Cannelli's documentation was deliberate advocacy in precisely this climate: a counter-narrative assembled to demonstrate the professional achievement, civic engagement, and cultural diversity and richness of a community that dominant American discourse refused to acknowledge. La Colonia Digital Archive makes that narrative searchable and accessible to researchers, descendants, and the general public, plotting archival documents and photographs onto contemporary maps of New Haven and the surrounding area. The archive is currently in active pre-launch development. Public release is planned for 2026, with ArcGIS StoryMap components to be added through 2026–2027.
Publication Title: Open MIND
Keywords: Cultural heritage; Digital Archives; Diversity (politics); Documentation; Haven; Narrative; dept.wll

Turning to returnees - Schmitt, Elena (Linguistic Approaches to Bilingualism, 2025)
Keywords: dept.wll

Humanistic Education: A Collection of Reflective Essays - Narvaez, George (Independently published, 2025)
Humanistic Education: A Collection of Reflective Essays by George Narvaez is a compelling anthology that bridges classical philosophy, modern educational theory, and personal reflection. Drawing on the author’s graduate studies at Harrison Middleton University, these twenty essays offer a deep dive into the evolution of human thought on education, knowledge, and the art of learning.This book is ideal for readers interested in the humanities, education, philosophy, or self-directed learning. It engages with timeless questions:What does it mean to “know” something?How is knowledge constructed and communicated?How can education empower individuals and communities?Inside this collection, you will explore:✔️ The foundational philosophies of Plato, Aristotle, Augustine, and Aquinas✔️ Modern insights from William James, John Dewey, and Benjamin Franklin✔️ The evolution of rhetoric and epistemology across history✔️ The relationship between language, culture, and cognition✔️ The author's transformative journey through educationEach essay combines academic rigor with accessible language, offering readers a path to understand how classical theories of liberal education connect with contemporary learning practices. From the “education of the hemispheres” in William James’s psychology to the experiential learning of Franklin and Dewey, the author shows that learning is not just about absorbing information—it’s about transforming the way we live, communicate, and understand ourselves and others.Key themes include:Rhetoric as a tool for empowermentEpistemology as a process of inquiryCivic responsibility through educationPersonal growth through humanistic reflectionWhether you're an educator, student, scholar, or lifelong learner, Humanistic Education is a thought-provoking guide to the intellectual traditions that continue to shape our educational ideals.Start your journey through the minds of history’s greatest thinkers—and reflect on your own learning path.

Bilingual autobiographical memory: unveiling the significance of memories encoded in multiple languages - Sorokina, Anastasia (Multilingua, 2025)
Keywords: Autobiographical memory; Cognitive psychology; Cognitive science; Computer science; Linguistics; Philosophy; Psychology; Recall; bilingual autobiographical memory; dept.wll; memory phenomenology; mixed memories; peer-reviewed

“It’s where she belongs, isn’t it?” Lupe Vélez and Dolores del Río in Hollywood - Hernández-Rodríguez, R. (Nomadic New Women: Exile and Border-Crossing between Spain and the Americas, Early to Mid-Twentieth Century, 2024)
Mexican artistic influence at the beginning of the twentieth century was prevalent in America, most notably muralism, but also talent associated with the movies. This influenced the way Mexico was perceived in the United States, and by extension the way Lupe Vélez and Dolores del Río, the most successful Mexican actresses in early Hollywood, were appreciated. Both actresses had come to Hollywood to fulfill their dream of a career in the movies. At first, they were successful playing a variety of roles in silent movies, but once sound arrived, their accents made obvious their foreignness at a time when American culture was beginning to spread around the world and to establish its preeminence. They were aware of the challenges they faced and knew there was a price to pay if they wanted to continue in a business where the public decided, at a time when Americans distrusted foreigners. So, if that price was to overplay her earthy Mexicaness, in the case of Vélez, or emphasize her aristocratic image, in the case of del Río, they were ready to pay it. Mexico became the other par excellence in the early twentieth century, and these heavily accented actresses were evidence of that.
Keywords: Dolores del Río; Ethnic representation; Hollywood; Identity; Lupe Vélez; Mexican influence; Silent films; Stereotypes; Talkies; dept.wll

Futurist arte / vita: Benedetta Fictionalized - Larkin, Erin (Volume 8 2018, 2018)
Keywords: dept.wll

Symbolic Violence and Public Displays of Difference - Compan, Magali (Visualizing Violence in Francophone Cultures, 2015)
Visualizing Violence in Francophone Cultures brings together two complex and powerful loci of meaning: violence and the visual. As such, it offers a comprehensive overview from which one can gain a better understanding of the complexity of the visual rhetoric of violence. The visual representations of violence explored in this volume include both fictional works, including, for example, narrative films, graphic novels, and theatre, and non-fictional genres, such as news media and cultural artifacts. This volume’s strength is also grounded in its interdisciplinary approach; by bringing together scholars from a variety of academic fields to examine a broad range of visual artifacts, such as photography, graphic novel, films, paintings, objects, the book offers a substantive corpus focusing on the rhetoric of violence. The essays collected in this volume explore the ways in which visual expressions of violence have infiltrated diverse narrative forms, and, as such, how they both construct and challenge general understandings of contemporary violence. They all chart, with cultural and historical specificity, the way in which images of violence shape the visual imaginary of ethical worlds.
Google-Books-ID: wqDWCgAAQBAJ
Keywords: History / General; dept.wll

Communicative relevance: Color references in bilingual and trilingual speakers - Pavlenko, Aneta; Jarvis, Scott; Melnyk, Svitlana; Sorokina, Anastasia (Bilingualism: Language and Cognition, 2017)
The study examined granularity of lexical partitioning of the blue area in speakers of English, which encodes the term blue; Russian, which encodes two terms, sinij [dark/navy blue] and goluboj [light/sky blue]; and Ukrainian, which encodes the terms synij [dark/navy blue] and blakytnyj and golubyj [light/sky blue]. Five groups of participants took part in the study: (1) 30 L1 speakers of English, (2) 30 L1 speakers of Russian, (3) 30 Russian–English bilinguals, (4) 30 English–Russian bilinguals, and (5) 25 Ukrainian–Russian–English trilinguals. Quantitative and qualitative analyses revealed that L1 Russian speakers referred to different types of blue significantly more frequently than all other groups, while bilinguals patterned with L1 English speakers. These findings suggest that classroom exposure to L2 Russian does not make the distinction between sinij and goluboj communicatively relevant for L1 English speakers and that everyday use of L2 English may trigger attrition of the contrast in L1 Russian.
Keywords: Russian; bilingual lexicon; color; communicative relevance; crosslinguistic influence; dept.wll

Challenges and achievements of an online intercultural exchange in time of crisis - Fornara, F; Gleason, Jesse (How We Take Action: Social Justice in PK-16 Language Classrooms, 2023)
How We Take Action brings together practical examples of social justice in language education from a wide range of contexts. Many language teachers have a desire to teach in justice-oriented ways, but perhaps also feel frustration at how hard it is to teach in ways that we did not experience ourselves as learners and have not observed as colleagues. As a profession, we need more ideas, more examples, and wider networks of allies in this work. This book includes the work of 59 different authors including teachers and researchers at every level from Pre-K to postsecondary, representing different backgrounds, languages, and approaches to classroom practice. Organized into three sections, some of the chapters in this collection report on classroom research while others focus on key practices and experiences. Section I is entitled Inclusive and Empowering Classrooms. In this section authors take a critical approach to classroom practices by breaking with the status quo or creating spaces where students experience safety, access, and empowerment in language learning experiences. Section II, Integration of Critical Topics, addresses a variety of ways teachers can incorporate justice-oriented pedagogies in day-to-day instructional experiences. Social justice does not happen haphazardly; it requires careful, critical examination of instructional practices and intentional planning as instructors hope to enact change. Section III, Activism and Community Engagement, explores how teachers can empower students to become agents for positive change through the study of activism and constructive community engagement programs at local and global levels.
Keywords: dept.wll

Embracing bilingualism: L1 retention amidst L2 acquisition - Sorokina, A.; Mugno, R. (Language Learning Journal, 2024)
In L1 attrition research, it's recognized that a previously acquired language can transform under the influence of a newly acquired one. However, the precise L1-L2 relationship is intricate and warrants further study. Some research suggest that L2 mastery might reduce L1 proficiency, while others show that both languages can be maintained. Age of onset and L1 use are the factors that have been discussed in the debate surrounding L1 attrition. The study aims to contribute to the ongoing discussion by examining L1 and L2 proficiency of Russian-English bilingual speakers (N = 35). The participants with comparable L2 proficiency but various degrees of L1 attrition who arrived at different ages and differed in their frequency of L1 use were recruited for the study. This diverse group provided an ideal quality sample for investigating the role of age of onset and L1 use, as well as the interplay between L1 and L2. By comparing L1 and L2 lexical diversity, syntactic complexity, and fluency, the study revealed that higher L2 proficiency was not associated with lower levels of L1 proficiency, suggesting that L1 retention is possible amidst L2 acquisition. L1 use played a more significant role in the L1 maintenance of these bilingual individuals. © 2024 Association for Language Learning.
Keywords: L1 attrition; L1 maintenance; L1 use; age of onset; bilingualism; dept.mat; dept.wll; peer-reviewed

A Century of Italian War Narratives: Voices from the Sidelines - Gussago, Luigi; Palma, Pina (Brill, 2023)
Keywords: Contemporary History; Criticism & Theory; Cultural History; History; Literary Relations; Literature and Cultural Studies; Memory Studies; dept.wll

A case study on the role of project-based learning in improving university students’ speaking skills: From theory to practice - Trihn, Nguyen Thi Tu; Schmitt, Elena (Konińskie Studia Językowe, 2020)
The aims of this paper are twofold: (1) to study the application of project-based learning ten-step process framework suggested by Alan and Stoller (2005) to boost English speaking ability of undergraduate students at the University of Da Nang, and (2) to investigate the levels of undergraduate students’ satisfaction. The subjects were 24 final year undergraduate engineering students at the university of Da Nang during the first semester of the 2019/2020 academic year. The instruments used in this experiment included lesson plans, a project evaluation form, a student’s self-assessment form, a satisfaction questionnaire and interviews
Keywords: English speaking skills; dept.wll; peer-reviewed; project-based learning; self-assessment

The knowledge framework for building teacher awareness of language in content instruction - Schmitt, Elena; Gleason, Jesse (Social Practices in Higher Education; A Knowledge Framework Approach to Linguistic Research and Teaching; Slater, 2023)
Keywords: dept.wll

Bilingualism - Schmitt, Elena G. (Encyclopedia of Slavic Languages and Linguistics Online, 2023)
Keywords: dept.wll

Report for Sabbatical Leave, Spring 2011. - Piemontese, Luisa (2011)
Studied contemporary poetry in Spanish by Spanish-speaking authors living in Connecticut. Works of four poets were chosen for a bilingual anthology. Seventy five percent of poems selected for this publication were translated and their analytical study completed. In addition, audio interviews were completed, and multimedia presentation, including photos, biographies, and bilingual readings was compiled and given. Publishing companies were identified for submission of the anthology's proposal.
Keywords: Connecticut; Poets; Spanish American; United States; dept.wll; faculty_collection; sabbatical_report

Modernity and Sexual Identity in Mexican Literature of the Early 20th Century. - Hernández, Rafael (2008)
Keywords: dept.wll; faculty_collection; sabbatical_report

Report of the Activities Completed During Sabbatical Leave in the Fall of 2007. - Schmitt, Elena (Distribution: Fall 2007 ; World Languages and Literatures., 2007)
Research completed during this leave focused on the already collected data for an article outlining distinctions between language attrition and incomplete acquisition, and on a new project and new data for research on how literacy or its lack in a minority language affects the degree of language maintenance and development.
Keywords: dept.wll; faculty_collection; sabbatical_report

Creating the Slavic Peril. - Paddock, Troy R. E. (2004)
Keywords: dept.wll; faculty_collection; sabbatical_report

The Literature of the Colombian Pacific Coast and the Construction of a Cultural Identity. - Arboleda, Carlos (2002)
Keywords: dept.wll; faculty_collection; sabbatical_report

Textual Experimentations in Contemporary Mexico. - Pelayo, Ruben (Fall;Foreign Language., 2001)
Keywords: dept.wll; faculty_collection; sabbatical_report

[Researched and translated two early twentieth-century plays] - Vena, Michael (Fall;Foreign Language., 2001)
Keywords: dept.wll; faculty_collection; sabbatical_report

[Wilhelm August Lehmann, 1870-1934] - Brockhagen, Marga (Fall;Foreign Language., 2000)
Keywords: dept.wll; faculty_collection; sabbatical_report

[Research on the Roman Historian Livy, Review of Ovid's Metamorphoses] - Solodow, Joseph B. (Spring;Foreign Language., 1999)
Keywords: dept.wll; faculty_collection; sabbatical_report

[Translation of two 20th century plays] - Vena, Michael (1995)
Keywords: dept.wll; faculty_collection; sabbatical_report

Study of Oral Tradition in the Work of Mariano Baselgu Ramirez. - Garcia-Abrines, Maria (1991)
Keywords: dept.wll; faculty_collection; sabbatical_report

Experience in the Visions of Hildegarde Von Bingen. - Brockhagen, Marga (1989)
Keywords: dept.wll; faculty_collection; sabbatical_report

Critique of a Play of Victor Hugo. - Ecklund, Constance (1989)
Keywords: dept.wll; faculty_collection

Esa Lluvia De Fuego Que Nos Quema. - Gaeda, Rita (1988)
Keywords: dept.wll; faculty_collection; sabbatical_report

Il piffero / the fife: raccolta - Di Pietro, Anthony (publisher not identified)
Keywords: dept.wll; faculty_collection

Ecocritical Reflections on Fiction Written by Nobel Laureate Mario Vargas Llosa - Flores, W. (Humanidades, 2023)
This article examines anthropocentric and ecocentric tendencies in two major works written by Mario Vargas Llosa, The Storyteller and The Dream of the Celt, to identify the value of those novels in ecocritical terms. I provide this analysis in the context of recent academic dialogue which notes an apparent contradictory relationship between the presentation of abuses of Amazonian people and their environment, and the portrayal of Westernized protagonists as their saviors in fiction written by Vargas Llosa. This essay provides a solution to this paradox and other apparent contradictions in his narratives and posits that even though the anthropocentric literary discourse concerning the environment has declined throughout the latter part of the twentieth century, in part, due to the rise of the environmental movement, this type of discourse has changed in Vargas Llosa’s literature, rejecting early twentieth century misconceptions of the natural world but holding onto technocentric neoliberal beliefs. © 2023, University of Montevideo. All rights reserved.
0 citations (Crossref) [2023-10-31]
Keywords: Mario Vargas Llosa; Peruvian literature; The Dream of the Celt; The Storyteller; dept.wll; ecocriticism; environment; peer-reviewed

Alsace and the French territorial debate: shifting the borders and discourses of regional and national identity - Eilderts, Luke L. (2019)
Keywords: dept.wll; faculty_collection; sabbatical_report

The Minor Tone of Desire - Barros, Pía; Cardone, Resha (Ediciones Sherezade, 2018)
Keywords: 21st century; Chilean fiction; Translations into English; Translations into English; Chilean fiction; Women authors; dept.wll; faculty_collection

De Connecticut a Salamanca: SCSU Program in Spain, 1990-2015, 25 Years of International Education Making a Difference - Arboleda, Carlos Arturo (Southern Connecticut State University, 2016)
Keywords: Connecticut; Southern Connecticut State University; International education; Spain; International education; dept.wll; faculty_collection

Sabbatical Leave Report. - Latorre, Sobeira (2015)
The objective of my sabbatical leave was to make progress on a book project tentatively entitled: "In conversation: Dominican women writers speak." This project is a book of interviews with contemporary women writers from the Dominican Republic as well as writers who identify themselves as Domincan-American...
Keywords: dept.wll; faculty_collection; sabbatical_report

Unbound and Underground: Chile's Ergo Sun Project from the Dictatorship to the Digital Era - Cardone, Resha (2014)
Cardone wrote chapters of a book manuscript and submitted two related articles to peer reviewed journals. She also transcribed and edited a scholarly interview, presented portions of book project at conference and traveled to site of book topic for on-ground research. Accomplishments are different than outlined in original proposal. The report describes project issues and results.
Keywords: dept.wll; faculty_collection; sabbatical_report

The Origins of Western Law from Athens to the Code Napoleon - Ecklund, John E. (Talbot Publishing, 2014)
Keywords: Europe; History; Law; Ancient; Law; Medieval; Law; dept.wll; faculty_collection; sabbatical_report

Modern Italian theater: (from Praga to Sciascia : text and context) - Vena, Michael (Xlibris LLC, 2014)
Keywords: 19th century; Theater; 20th century; Italy; Theater; dept.wll; faculty_collection

Italian Playwrights from the Twentieth Century: A Companion Text - Vena, Michael (Xlibris Corporation, 2013)
Keywords: 20th century; History and criticism; Italian drama; dept.wll; faculty_collection

Los Que Sobran = Those Not Spared - Barros, Pía (Asterión, 2010)
Keywords: 21st century; 21st century; Chilean fiction; Chilean fiction; Translations into English; Translations into English; Chilean fiction; Women authors; Women authors; Chilean fiction; dept.wll; faculty_collection

A Revolution of Shadows: Culture and Representation in Early-Twenieth-Century Mexico - Hernández Rodríguez, Rafael (The Popular Avant-Garde, 2010)
The avant-garde has been popular for some time, but its popularity has tended to fly under the radar. This “popular avant-garde,” conceived as the meeting ground of the avant-garde and popular, avoids the divorce of art and praxis of which the avant-garde has been accused. The Popular Avant-Garde takes stock of the debates about both the “historical” (“modernist”) and posterior avant-gardes, and sets them in relation to popular culture and art forms. With a critical introduction that examines the concepts of “the avant-garde,” “the popular,” and “the popular avant-garde,” the series of essays analyzes the way in which the avant-garde employs popular genres for political purposes, as well as how the popular acquires a critical function with respect to the avant-garde. Each of the volume’s three sections considers a different aspect of the productive exchange between the avant-garde and popular: the popular avant-garde as a culturally hybrid and cross-border phenomenon; the play between the popular avant-garde and developments in media and technology; and the popular avant-garde’s upending of conventional ideas about “the people” and “the popular.” The Popular Avant-Garde takes a fresh look at the now canonical Dadaist, Futurist, and Surrealist movements from the perspectives of gender and sexuality, and cultural and critical theory, while at the same time exploring less well-known avant-garde work in literature, film, television, music, photography, dance, sculpture, and the graphic arts. This volume’s coverage of the American and Afro-American, Luso-Brazilian and Latin-American, East-European, and Scandinavian avant-gardes, in addition to the vanguards of Spain and other parts of Western Europe, will appeal to all those interested in avant-garde and popular art forms.
Keywords: Avant-garde (Aesthetics); Popular culture; dept.wll; faculty_collection

Gabriel García Márquez: A Biography - Pelayo, Rubén (Greenwood Press, 2009)
Keywords: 20th century; Biography; García Márquez; Gabriel; 1927-2014; Authors; Colombian; dept.wll; faculty_collection

Inclusive Pedagogy for English Language Learners: A Handbook of Research-Informed Practices - Verplaetse, Lorrie Stoops; Migliacci, Naomi (Lawrence Erlbaum Associates, 2008)
Keywords: English language; Foreign speakers; English language; Foreign speakers; Language and languages; Study and teaching; Study and teaching (Elementary); Study and teaching (Secondary); dept.wll; faculty_collection

The impact of Don Quixote (1605-2005) on the culture of the modern and postmodern world: proceedings of the Southern Connecticut State University International Conference on Don Quixote, New Haven, April 22-23, 2005 - Southern Connecticut State University International Conference on Don Quixote New Haven, Conn) (Southern Connecticut State University, 2006)
Keywords: Cervantes Saavedra; Miguel de; 1547-1616. Don Quixote; Congresses; Postmodernism; dept.wll; faculty_collection

Agítese Bien: A New Look at the Hispanic Avant-Gardes - Pao, María T.; Hernández Rodríguez, Rafael (Juan de la Cuesta, 2002)
Keywords: 20th century; History and criticism; History and criticism; Latin American literature; History and criticism; Literature; Experimental; History and criticism; Spanish American literature; Latin America; Spain; Spanish literature; dept.wll; faculty_collection

Gabriel García Márquez: A Critical Companion - Pelayo, Rubén (Greenwood Press, 2001)
Keywords: Criticism and interpretation; García Márquez; Gabriel; 1927-2014; dept.wll; faculty_collection

Italian Grotesque Theater - Vena, Michael (Fairleigh Dickinson University Press, 2001)
SCSU Faculty Scholar Award
Keywords: 20th century; History and criticism; Grotesque in literature; Italian drama; award_winner; dept.wll; faculty_collection

Second and Foreign Language Learning Through Classroom Interaction - Hall, Joan Kelly; Verplaetse, Lorrie Stoops (Erlbaum, 2000)
This volume brings together the current theoretical interest in reconceptualizing second and foreign language learning from a sociocultural perspective on language and learning, with practical concerns about second and foreign language pedagogy. It presents a set of studies whose focus is on the empirical description of particular practices constructed in classroom interaction that promote the learning of a second or foreign language. The authors examine in detail the processes by which the learning of additional languages is accomplished in the interaction of a variety of classrooms and in a
Keywords: Language and languages; Study and teaching; Interaction analysis in education; dept.wll; faculty_collection

Poemas de New England - Geada, Rita (Indian Hill Press, 1996)
Keywords: Poetry.; dept.wll; faculty_collection

Offprint of Italian Literature: Roots and Branches: Essays in Honor of Thomas Goddard Bergin - Bergin, Thomas Goddard; Rimanelli, Giose; Atchity, Kenneth John (Yale University Press, 1976)
Vena, Michael. Alberti's linguistic innovations.
Keywords: dept.wll; faculty_collection

The Importance of the Spanish Language for North Americans - Méndez-Peñate, Sergio A. (s.n., 1972)
Keywords: Spanish language; United States; dept.wll; faculty_collection

The Spanish and Spanish-American Novel - Méndez-Peñate, Sergio A. (s.n., 1972)
Keywords: History and criticism; History and criticism; Spanish American fiction; Spanish fiction; dept.wll; faculty_collection

Intermediate German. - Werba, Henry (Holt, Rinehart and Winston, 1971)
Keywords: English; German language; Textbooks for foreign speakers; dept.wll; faculty_collection

Marcel Aymé et le Merveilleux. - Dumont, Jean-Louis (Debresse, 1970)
Keywords: Aymé; Marcel; 1902-1967; Marvelous; The; in literature; dept.wll; faculty_collection

Voices in Dialogue: Reading Women in the Middle Ages - Olson, Linda; Kerby-Fulton, Kathryn (University of Notre Dame Press, 2005)
Keywords: History; History and criticism; Civilization; Medieval; Middle Ages; 500-1500; Women and literature; To 1500; Literature; Medieval; Women; dept.wll; faculty_collection

Children, Schools, and Inequality - Entwisle, Doris R.; Alexander, Karl L.; Olson, Linda Steffel (Westview Press, 1997)
Keywords: Baltimore; Education; Elementary; Longitudinal studies; Longitudinal studies; Education; Elementary; Longitudinal studies; Educational equalization; Longitudinal studies; Observation (Educational method); Maryland; Social aspects; dept.wll; faculty_collection

Dictionary of Twentieth-Century Cuban Literature - Martínez, Julio A. (Greenwood Press, 1990)
Keywords: 20th century; Bio-bibliography; Cuban literature; Dictionaries; Dictionaries; Cuban literature; History and criticism; dept.wll; faculty_collection

Sabbatical leave report: Fall 2014 - Cardone, Resha (2014)
Cardone wrote chapters of a book manuscript and submitted two related articles to peer reviewed journals. She also transcribed and edited a scholarly interview, presented portions of book project at conference and traveled to site of book topic for on-ground research. Accomplishments are different than outlined in original proposal. The report describes project issues and results. Book title is "Unbound and underground: Chile's Ergo Sun Project from the dictatorship to the digital era."
Keywords: dept.wll; faculty_collection; sabbatical_report

Coping with a language loss: A case of linguistic and cultural re-encoding of memories in language attriters - Sorokina, Anastasia (International Journal of Bilingualism, 2023)
Aims and objectives:This study investigates the effects of language loss on bilingual autobiographical memory. More specifically, the study focuses on whether severe language loss would lead to any linguistic changes and/or interfere with how memories are recalled and shared.Methodology:Autobiographical memories were elicited with the help of a cued-recall technique and memory questionnaire from two groups of immigrants?attriters (who experienced significant language loss) and bilinguals (who retained their first language proficiency).Data and analysis:The data set consisted of pre-immigration memories that were originally encoded in the first language, Russian. The frequency of recall (i.e., sharing memories with others as well as reminiscing) and linguistic components (i.e., words) of memories elicited from the attriters and bilinguals were analyzed quantitatively and qualitatively.Findings and conclusion:Overall, attriters were able to recall memories that were originally encoded in the forgotten language. They also reported reminiscing about their pre-immigration memories and sharing their memories with others. However, attriters revealed that the pre-immigration memories came to them with words in the second language, English, which was not the case with bilinguals. Attriters also reframed memories for several Russian culture-specific items and events. This finding is indicative of memory re-encoding?a phenomenon when memories are updated, stored, and subsequently retrieved with added information. While this finding points to the bilingual mind?s ability to adapt to language loss, it may also suggest linguistic and cultural assimilation under the influence of the new language and culture.Originality:This is the first investigation of autobiographical memory in bilinguals with severe language loss that highlights the malleability and adaptability of the bilingual mind as well as the importance of language maintenance.
0 citations (Crossref) [2023-10-31]
Keywords: dept.wll; peer-reviewed

Of courtesans, knights, cooks and writers: Food in the renaissance - Palma, P. (MLN - Modern Language Notes, 2004)
0 citations (Crossref) [2023-10-31]
Keywords: dept.wll

Why did the monkey kill the giant? Another look at Margutte's death - Palma, P. (Quaderni d'Italianistica, 2010)
In the Morgante through Margutte's death-by-laughter Pulci voices a caustic critique of Ficino's philosophical theories while obliquely denouncing Lorenzo de Medici's acceptance of them. The spectacle of the monkey wearing and taking off Margutte's boots follows Aristotle's definition of the ridiculous that ignites hilarity. It also retrieves Bergson's idea of a society that can be derided because of its attempts to disguise its true self. Most importantly, it reintroduces Petrarch's concepts of similitudo and identitas. Through the depiction of the giant's death Pulci reveals the dignity of a poet remaining true to his poetic discourse even while coming to terms with the negative turn his career has taken.
0 citations (Crossref) [2023-10-31]
Keywords: dept.wll

Jews and Jewishness in Carme Riera‘s Dins el darrer blau - Sosa-Velasco, A.J. (Iberian Modalities: A Relational Approach to the Study of Culture in the Iberian Peninsula, 2010)
Las hogueras del fanatismo y la ortodoxia son una constante del siglo XXI, en el que ya estamos. Seguimos proyectando nuestro peor yo sobre los débiles, los pobres y los emigrantes. Necesitarí amos matar el yo racista que llevamos dentro y eso sólo se puede conseguir colocándonos en el lugar del otro, sintiéndote agredida. In the last twenty-five years, Jews have emerged as a literary figure as well as a literary theme in Spain. Catalan writers such as Maria Àngels Anglada (1930- 99), Carme Riera (1948–), and Vicenç Villatoro (1957–) approach the Jewish theme and the representation of the Jew as literary character in order to reflect on issues regarding identity and history in novels, such as El violí d‘Auschwitz (1994), Dins el darrer blau (1994), and Memòria del traïdor (1996), respectively. With Dins el darrer blau, written between 1989 and 1993, published in Catalan in 1994 and in Castilian in 1996, Riera starts a series of novels dedicated to the Majorcan xuetes (Jews who were converted to Christianity) which she finishes with Cap al cel obert in 1999. In this essay I will reflect on how Riera‘s Dins el darrer blau revisits the past in order to create a “culture of memory,” a process in which society confronts its traumatic past and the history of exile and repression, linking the history of the Jewish converts to the history of the Balearic island, Majorca. Riera‘s novel is based on historical events that occurred in the City of Majorca from 1687 to 1691. © 2013 Liverpool University Press.
Journal Abbreviation: Iber. Modalities: A Relat. Approach to the Study of Cult. in the Iber. Penins.
Keywords: dept.wll

Refashioning the book in Pinochet's Chile: The feminist literary project. Ergo Sum - Cardone, R. (Confluencia, 2013)
Keywords: dept.wll; ⛔ No DOI found

Savoring Power, Consuming the Times: The Metaphors of Food in Medieval and Renaissance Italian Literature - Palma, Pina (University of Notre Dame Press, 2013)
"Pina Palma's Savoring Power, Consuming the Times: The Metaphors of Food in Medieval and Renaissance Italian Literature is an innovative look at the writings of five important Italian authors–Boccaccio's Decameron, Pulci's Morgante, Boiardo's Innamorato, Ariosto's Furioso, and Aretino's Ragionamento. Through the prism of gastronomy, Palma examines these key works in the Western literary canon, bringing into focus how their authors use food and gastronomy as a means to critique the social, political, theological, philosophical, and cultural beliefs that constitute the fabric of the society in which they live." – Publisher's website.
SCSU Faculty Scholar Award
Keywords: 16th century; History and criticism; Food in literature; Gastronomy in literature; History and criticism; Italian literature; Italian literature; SCSU Faculty Scholar Award; To 1400; award_winner; dept.wll; faculty_collection

Fairness - Scott Walters, F. (The Routledge Handbook of Language Testing, 2013)
Among language testing researchers, the notion of fairness has accumulated a number of complex, technical definitions over the years. However, since the word has such a widespread, everyday usage, consulting a dictionary can be a good starting-point for discussion. For example, YourDictionary.com (2011) states that to be fair is to be “just and honest,” “impartial,” and “unprejudiced,” specifically, “free from discrimination based on race, religion, sex, etc.“Merriam-Webster (Mish et al., 2003) states similarly that fairness is “marked by impartiality or honesty” and is “free from self-interest, prejudice, or favoritism.” As this volume deals with second/foreign/other language testing, it would seem appropriate (or perhaps one should say, fair) to include a dictionary definition crafted for L2 learners, as is this one from Cambridge (Walter et al., 2006): “Treating someone in a way that is right or reasonable, or treating a group of people equally and not allowing personal opinions to influence your judgment.”. © 2012 Selection and editorial matter, Glenn Fulcher and Fred Davidson.
Journal Abbreviation: The Routledge Handb. of Language Test.
Keywords: dept.wll

Shifting paradigms: A model for the integrated assessment of language and culture - Hammer, J.; Schmitt, E. (Culture and Foreign Language Education: Insights from Research and Implications for the Practice, 2015)
Journal Abbreviation: Cult. and Foreign Lang. Educ.: Insights from Res. and Implic. for the Pract.
Keywords: dept.wll

Food Cultures of Mexico: Recipes, Customs, and Issues - Hernández Rodríguez, Rafael (Greenwood, an imprint of ABC-CLIO, 2021)
"This exciting volume brings to life the food culture of Mexico, detailing the development of the cuisine and providing practical information about ingredients and cooking techniques so that readers can replicate some of Mexico's most important traditional dishes"–
Google-Books-ID: mppBEAAAQBAJ
Keywords: Cooking / Regional & Ethnic / Central American & South American; Cooking / Regional & Ethnic / Mexican; Food habits; History / Latin America / Mexico; Mexico; Cooking; Mexican; Mexico; Social life and customs; dept.wll

Developing self-directed learning strategies through creative writing: Three case studies of snowball writing practice in a college Chinese language classroom - Tu, I. Ju (Thinking Skills and Creativity, 2021)
This study investigates three learners’ self-directed learning (SDL) strategies in a college beginner level Chinese language classroom. Using a focus group and interviews to explore how the students recognize their own learning strengths and weaknesses, what strategies they develop during the SDL process, their awareness of learning contexts while adopting SDL, and how they exercise their agencies for SDL. Findings suggest that technology fluency, the disconnection between learning goals and SDL strategies, and learners’ unawareness of their learning strengths affects individuals’ agency regarding SDL strategies. These findings suggest the need for further discussion of language teachers’ role in instructing SDL strategies, the role of technology, and the use of written corrective feedback. © 2021
3 citations (Crossref) [2023-10-31]
Keywords: dept.wll; peer-reviewed

Empirical insights into college students’ academic reading comprehension in the united states - Kalbfleisch, Elizabeth; Schmitt, Elena; Zipoli, Richard P. (Journal of College Reading and Learning, 2021)
This article reports on a collaborative research project involving faculty in writing studies, communication disorders, and applied linguistics that sought to empirically describe the reading skills of students (N = 910) in freshman composition classes at one college and two universities in the northeast United States. The research team developed and administered a questionnaire that evaluated students’ reading abilities according to six categories: inferential ability, background knowledge, general comprehension, vocabulary, figurative language/jargon, and morphosyntactic structures (grammar/syntax). Our statistically significant results showed that students scored best in the categories of background knowledge and general comprehension, which are well researched in a college population. However, students struggled in categories such as figurative language/jargon and morpho-syntactic structures, which are not well researched in a college population. Further, comprehension seemed generally discrete (understanding specific points of an essay) rather than holistic (indicated by an ability synthesize those points into a general statement about the author’s thesis). These findings suggest that further empirical research in this area will help describe the reading skills of college students and consequently will inform the development of pedagogical approaches that more effectively address students’ current needs. © 2021 College Reading and Learning Association.
2 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85101017685
Keywords: dept.cmd; dept.eng; dept.wll; peer-reviewed

Satire, ecocentrism, and luddite discourse in One Hundred Years of Solitude: regional approaches for a global environmental crisis - Flores, William (Gabriel García Márquez in Retrospect: A Collection, 2016)
Gabriel Garcia Marquez in Retrospect gathers fifteen essays by noted scholars in the fields of Latin American literature, politics, and theater. The volume offers broad overviews of the Colombian author’s total body of work, along with closer looks at some of his acknowledged masterpieces. The Nobel laureate’s cultural contexts and influences, his variety of themes, and his formidable legacy (Hispanic, U.S., world-wide) all come up for consideration. New readings of One Hundred Years of Solitude are further complemented by fresh, stimulating, highly detailed examinations of his later novels (Chronicle of a Death Foretold, The General in His Labyrinth, Of Love and Other Demons) and stories (Strange Pilgrims). Further attention is focused on “Gabo’s” labors as journalist and as memoirist (Living to Tell the Tale), and to his sometime relationships with the cinema and the stage. Reactions to his enormous stature on the part of younger writers, including recent signs of backlash, are also given thoughtful scrutiny. Feminist and ecocritical interpretations, plus lively discussions of Gabo’s artful use of humor, character’s names, and even cuisine, are to be found here as well. In the wake of García Márquez’s passing away in 2014, this collection of essays serves as a fitting tribute to one of the world’s greatest literary figures of the twentieth century.
Google-Books-ID: TgjWDQAAQBAJ
Keywords: Literary Criticism / Caribbean & Latin American; Literary Criticism / General; Literary Criticism / Modern / 20th Century; dept.wll

Redemptive children and historical memory: Luis mateo díez’s la gloria de los niños (2007) - Weng, Miaowei (Bulletin of Spanish Studies, 2020)
This article explores contemporary Spanish writer Luis Mateo Díez’s 2007 novel, La gloria de los niños, focusing on the construction of a redemptive child who mends the broken world and keeps alive historical memory. The author looks beyond one single nation state in his reconstruction of children and childhood under the Franco regime. Hidden behind his approach to the reconstruction of the ‘glorious children’ under Franco emerges, on the one hand, his dissolution of any authoritative version of Franco-era children and, on the other, his broader vision and desire to examine Spain and Spanish historical memory in a global context. © 2020 Bulletin of Spanish Studies.
0 citations (Crossref) [2023-10-31] tex.ids: wengRedemptiveChildrenHistorical2020 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85095847122 type: Article
Keywords: Childhood under Franco; Historical Memory; La gloria de los niños; Ladri di biciclette (1948); Luis Mateo Díez; Post Civil War period; Redemptive Child; Vittorio de Sica; Walter Benjamin; dept.wll; peer-reviewed

French accent through video analysis - Ecklund, Constance L; Wiese, Peter (Foreign Language Annals, 1981)
Abstract Evaluating a student's accent in a foreign language is a complex process. Although it is obvious to the instructor whether or not the sound is correct, it is difficult for students both to hear the incorrect sound and to correct it. Too often the instructor merely tells the students that they have spoken incorrectly, expresses the sound properly, and then tries, often without lasting success, to have the students imitate. In a phonetically oriented course, diagrams are used as visual aids to teach correct articulation; but, especially at lower levels, it is difficult and often uninspiring for students to identify their speech production with such text figures. In a new method an improvised television “studio” captures the individual student's speech in an easily reviewable, permanent form on videotape. This visual, personal approach can make spectacular improvement in pronunciation, and the technique appears to be adaptable to any level of language learning. © 1981 American Council on the Teaching of Foreign Languages
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/033-131-487-553-974 tex.type: [object Object]
Keywords: dept.wll

The evolving door: providing technology access for post-secondary students in a constantly changing technology-based culture - Hecht, Janice; Zamfir, Bogdan (International Conference on Computers Helping People with Special Needs, 2002)
The Center for Adaptive Technology at Southern Connecticut State University was established in 1988 to provide access to computers for students with disabilities. The challenge of keeping current with both standard and adaptive technology has caused our service to evolve from a focused, centralized model to an integrated model providing technology access to students regardless of their location on campus. © Springer-Verlag Berlin Heidelberg 2002.
0 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Adaptive technology; Artificial intelligence; Centralized models; Computer science; Computers; Integrated modeling; Students; Technology-based; dept.wll

Fifty Strategies for Teaching English Language Learners.: Adrienne L. Herrell - Reynolds, Kate Mastruserio (TESOL Quarterly, 2001)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000168531300015, lens.org/044-748-807-257-656, pop00009 tex.unique-id: [object Object]
Keywords: dept.wll

Out of Africa - Feinberg, H.M.; Solodow, J.B. (Journal of African History, 2002)
This article traces the origins of the familiar quotation, 'there is always something new coming out of Africa'. It demonstrates that the phrase was a proverb that originated in Greece no later than the fourth century BC. It charts the transmission of the phrase from Aristotle to the twentieth century, noting that Erasmus is the most important link in the Renaissance and that he may be responsible for the current form in which the phrase is used. The article also shows that the meaning of the phrase was very different in ancient times from what it is today. Whereas 'something new' to Aristotle meant strange hybrid animals, current writers use the phrase with a sense of admiration.
9 citations (Crossref) [2023-10-31]
Keywords: Africa; Historiography; dept.his; dept.wll; history; perception; regional geography

Inventing the self, fictionalizing the other: false memories in the theatre of mario vargas llosa - Melendez, Priscilla (Symposium: A Quarterly Journal in Modern Literatures, 2012)
The Peruvian writer Mario Vargas Llosa, one of the most prolific and distinguished Spanish American novelists of the twentieth century and the winner of the 2010 Nobel Prize in Literature, is also the author of eight plays, which have frequently been overshadowed by his narrative production. Going beyond the relationship traced by critics between his novels and his plays, this essay underscores the prevalence in his theatrical work of a tug of war between biographical and autobiographical voices as part of a fundamental exploration of real and fictional memory. From Vargas Llosa's early plays of the 1980s to his most recent ones, he has frequently dramatized the life of both real and imaginary, famous and infamous others and selves, creating the illusion that the audience is witnessing someone's life trajectory. This is the analytical angle from which this essay approaches not only Vargas Llosa's first play, La seorita de Tacna (1981), but in particular one of his most recent ones, Odiseo y Penélope (2007). In both analyses, the definitions of biographical and autobiographical discourses are interpreted in light of theatrical representation, underscoring in this way the subjective, dramatic, and metaphorical perspectives of these expressions. © 2012 Taylor and Francis Group, LLC.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/013-132-663-189-569
Keywords: La seorita de Tacna; Odiseo y Penélope; Vargas Llosa; autobiography; dept.wll; theatre

Students in the new millennium: how much do we know about them? - Wu, Jianxiong (Computer-Assisted Foreign Language Teaching and Learning: Technological Advances, 2013)
Vast and fast technological advancements mark the new millennium. New emerging technologies are changing the world and our society at a magnitude and scope never witnessed before. Who are our students in this new millennium? What do they look like? Are they a fundamentally different new generation as some claim, or do they still look similar to us in many ways? A clear understanding of the characteristics of our students is vitally important for our educational practice. The current study was conducted to contribute to this understanding. The findings of the study show that while students nowadays do enjoy a much broader access to new technology than students of the past, they still look similar to us in many ways. As educators, it is important for us to treat our students as individuals instead of just labeling them and placing them in a black and white dichotomy.
Citation Key Alias: lens.org/016-023-260-719-437
Keywords: Emerging technologies; Students; Technological advancement; Technology transfer; dept.wll

Meaning-based scoring: A systemic functional linguistics model for automated test tasks - Gleason, Jesse (Hispania-a Journal Devoted to the Teaching of Spanish and Portuguese, 2014)
Communicative approaches to language teaching that emphasize the importance of speaking (e.g., task-based language teaching) require innovative and evidence-based means of assessing oral language. Nonetheless, research has yet to produce an adequate assessment model for oral language (Chun 2006; Downey et al. 2008). Limited by automatic speech recognition (ASR) technology, which compares non-native speaker discourse to native-like discourse, most tests exclusively focus on accuracy while ignoring how examinees use language to make meaning. In order to offer stakeholders more trustworthy evidence of how examinees might use language in target language domains, a model anchored in systemic functional linguistics (SFL) is put forth. Specific examples are given of how SFL might be used to evaluate test task types, such as the story retell:three examinees' responses are contrasted using genre analysis (Derewianka 1990) and transitivity analysis (Ravelli 2000) in order to demonstrate elements in their linguistic profiles that ASR-based assessment would overlook. In so doing, implications are drawn regarding the potential of SFL models for enhancing automated scoring procedures by focusing on the meaning-form relations in the linguistic construction of narrative.
7 citations (Crossref) [2023-10-31] tex.eissn: 2153-6414 tex.unique-id: ISI:000345494100012
Keywords: Adult Spanish literacy alfabetización adulta de español; Automated language assessment evaluación automática del lenguaje; Discourse analysis análisis del discurso; Systemic functional linguistics lingüística sistémico-funcional; Transitivity analysis análisis de transitividad; dept.wll; peer-reviewed

Using big questions to apprentice students into language-rich classroom practices - Verplaetse, Lorrie Stoops (TESOL Quarterly, 2014)
10 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/067-055-821-290-826 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.wll

“It helps me get closer to their writing experience” Classroom ethnography and the role of technology in third-year FL courses - Gleason, Jesse (System, 2014)
Research has shown a disjunction between language instruction at the lower and upper levels of foreign language (FL) study. Whereas lower-division courses focus on grammatical patterns, upper-level courses focus on specific content. The third-year writing course is in a unique position to help learners prepare for the types of learning that they will encounter in more advanced language use contexts. Using grounded classroom ethnography, this multiple case study of two classrooms chronicles how a collaborative partnership between an instructor and an applied linguist facilitated the integration of two types of technology into a third-year Spanish writing course at a North American University. Technology was carefully chosen based on pedagogical considerations and teacher goals. Students in these courses included a mixture of heritage and FL Spanish learners with a mean age of 21 years. Findings included four ways that technology played a role in third-year Spanish language learning, including as: (a) a way to alleviate their workloads, (b) a motivator, (c) a way to improve the quality and quantity of feedback students received in the course, and in some cases (d) antagonistic to language learning. Implications of classroom ethnography for research on blended learning are drawn. Published by Elsevier Ltd.
4 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000345155800012, lens.org/016-859-492-698-057 tex.type: [object Object]
Keywords: Blended language learning; Discourse analysis; Ethnography; Language-content gap; Spanish; Teacher-researcher collaboration; Technology; Third-year FL courses; Writing; dept.wll

Developing cultural humility through critical service learning - Breda, Karen Lucas; Groot, Kim; Towle, Antoinette (Ciencia y enfermería, 2013)
Marked inequities or disparities in health care and health outcomes exist for millions in the United States of America. Urban apartheid and increasing social stratification separate social groups making it difficult for them to understand each other. Many U.S. health care professionals, including nurses, hold negative stereotypes toward the urban poor and disenfranchised. Creating vehicles for understanding and respect between health care professionals and the social groups they care for is needed. Cultural humility uses self-reflection, self-critique, openness and transcendence to address power inequities between providers and clients. "Critical service-learning" is a type of "service-learning" that adopts the tenets of critical theory and pedagogy in engaged partnerships to foster social responsibility and a justice-oriented framework. The purpose of this article is to showcase Project Horizon, an innovative university-based health and social advocacy partnership that uses critical service learning with the urban community to foster cultural humility. Project Horizon outcomes show that this long-term engaged partnership is an effective vehicle for developing and enhancing cultural humility among health care professionals participating in the endeavor. Implications: Replication of social and health advocacy projects such as the one conducted through Project Horizon can be made in other settings to increase the capacity for democratically oriented nurses and other health care professionals who have an enhanced sense of cultural humility.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/076-789-415-089-173
Keywords: Critical service learning; Cultural humility; Health consortia; Health personnel; Healthcare disparities; dept.wll

Benedetta and the creation of ‘Second Futurism’ - Larkin, Erin (Journal of Modern Italian Studies, 2013)
Despite the recent vogue in studies on Futurism, writer and artist Benedetta Cappa Marinetti has received little critical attention. Few scholarly works have focused on her essays regarding woman and the Fascist state, and in particular the role of mother. It has been argued that these texts support not only the position that women futurists - in adhering to a movement remembered for its disprezzo della donna - were victims of their self-accepting inferiority, but also the view that Futurist attitudes towardswomen were a precursor of Fascist-era gender politics. Larkin challenges this position, and discusses crucial new archival research, which reveals how maternity in Benedetta's works is actually linked to her radical new reformulation of Futurism. Far from seconding woman's inferior position within the avant-garde, or indeed the Fascist state, Benedetta uses the issue of maternity subtly to subvert her status - in both the movement and society - from within. © 2013 Taylor & Francis.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/102-795-659-868-757 tex.type: [object Object]
Keywords: Avant-garde; Benedetta; Cappa; Futurism; Marinetti; Women writers; dept.wll

Assessing strategic cultural competency: holistic approaches to student learning through media - Hammer, Judith; Swaffar, Janet (The Modern Language Journal, 2012)
The current study investigated the impact of a German television program on changes in 4th-semester German students' reflections on cultural perceptions over the course of 1 semester. Sixty-nine students at the University of Texas at Austin watched 4 episodes of the popular German television program Lindenstrasse. After viewing, students were asked to reflect in written response papers on cultural features and patterns of behavior and on cultural differences and similarities. The study results suggest that students' perceptions of another culture can become more sophisticated when being exposed to authentic filmic material and asked to reflect in writing about observed plot features and cultural manifestations. The key to these results is a strategy for assessing not just students' recall of cultural content, but also their strategic competencies in negotiating cultural difference. Changes in students' cognitive styles were tracked by a scale that rewards students' strategic ability tomanage details of cultural knowledge and sociolinguistic content, including the following categories: (a) rhetorical organization; (b) content; (c) comparative point of view; and (d) interpretive substance. The article provides a model for the assessment of cultural competency (MACC), which can be adapted to assess students' engagement with the culture represented in various materials.
14 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/036-725-840-773-327 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.wll

Utopian worlds: vico, la capria and mazzotta - Palma, Giuseppina (MLN - Modern Language Notes, 2012)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/014-683-427-020-179 tex.type: [object Object]
Keywords: dept.wll

Bilingualism and Learning - Verplaetse, L. S.; Schmitt, E. (International Encyclopedia of Education (Third Edition), 2010)
Bilingualism is defined as a speaker's ability to use two languages for communication. Due to the complexity of its nature, the study of bilingualism relies on several fields within linguistics, anthropology, psychology, neuroscience, and education. The study of bilingualism describes language behaviors of bilingual speakers, social and pragmatic patterns of using two languages, language development, and acquisition and loss, among other issues. Researchers attempt to explain the effect that bilingualism has on human cognition, societal relationships, and education of bilingual children. This article discusses bilingualism and learning from three perspectives: types of bilingualism, bilingual processing, and bilingualism and academic learning.
Citation Key Alias: lens.org/011-256-520-522-91X, pop00385
Keywords: Academic language; Additive bilingualism; Anomie; Balanced bilingualism; Bilingualism; Code switching; Diglossia; Immersion model; Maintenance bilingual (education); Semilingualism; Sequential bilingualism; Sheltered content (instruction); Simultaneous bilingualism; Societal bilingualism; Subtractive bilingualism; Transitional bilingual (education); dept.wll

When boundaries are crossed: Evaluating language attrition data from two perspectives - Schmitt, Elena (Bilingualism: Language and Cognition, 2010)
This study provides an account for a long-term selective loss of L1 (Russian) morpho-syntactic and content components in early immigrants to the US. The analysis of naturally occurring data is carried out from the perspective of two theoretical approaches - three models developed within language contact (Myers-Scotton 2002, 2005) and the Activation Threshold hypothesis as a component of a neurolinguistic approach to bilingualism (Paradis, 2004, 2007). The results show that the language contact approach is useful in identifying morpheme types that are most vulnerable to attrition. The second approach helps explain the differential rate of loss of content morphemes in a variety of topics and account for variability in the rate of attrition of late system morphemes through frequency factors. The study demonstrates that by crossing the boundaries of one theory, and one view of language researchers can achieve a stronger explanatory power and identify the common and complementary features that both models provide.
14 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/038-866-199-464-167 tex.unique-id: [object Object]
Keywords: dept.wll

The knowledge framework for building teacher awareness of language in content instruction - Gleason, Jesse; Schmitt, Elena (Social practices in higher education - A knowledge framework approach to linguistic research and teaching, 2021)
Keywords: dept.wll; faculty_collection

Promoting social justice with CALL - Gleason, Jesse; Suvorov, Ruslan (CALICO Journal, 2018)
11 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/006-216-002-732-944, pop00223 tex.type: [object Object]
Keywords: dept.wll; peer-reviewed

Farewell to Naples: Ferrante’s 'Story of a New Name' - Palma, Pina (Forum Italicum: A Journal of Italian Studies, 2018)
In Ferrante’s Story of a New Name, the protagonist’s journey to self-knowledge and self-realization is mapped through a farewell trip to Naples before she begins her studies in Pisa. As the centerpiece and background around and against which Elena’s accomplishments, failures, and societal pressures revolve, Naples emerges as a mosaic of energy and lethargy, unbreakable traditions and negligible innovations. While these elements mirror the protagonist’s powerlessness in changing the “norms” to which she is expected to adhere, they also function as her spur to a steady shift toward self-understanding. In this article, I analyze the ways in which Ferrante’s use of the beauty and lure, corrosiveness and lethality of Naples parallel her discourse on the protagonist’s search for self-understanding, a process that will ultimately enable Elena, the protagonist, to find self-realization. © 2018, The Author(s) 2018.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/059-690-228-679-585, pop00335 tex.type: [object Object]
Keywords: authorship; dept.wll; labyrinth; memory; peer-reviewed; reading; self-fulfillment; self-knowledge; urban space

The devil and the mirror: Pulci’s theology - Palma, Pina (Luigi Pulci in Renaissance Florence and Beyond, 2018)
Keywords: dept.wll

Connected classrooms: Videoconferencing in TESOL teacher preparation - Schmitt, Elena; Eilderts, Luke (International Journal of Teaching and Learning in Higher Education, 2018)
Keywords: dept.wll; peer-reviewed; ⛔ No DOI found

Class, generation, and gender in Esther Tusquets's Habíamos Ganado La Guerra: Reflections on the winning of the Spanish Civil War - Weng, Miaowei (Hispanófila, 2018)
0 citations (Crossref) [2023-10-31]
Keywords: dept.wll; peer-reviewed

Patterns of oral choice and evaluation across secondary content areas. - Gleason, Jesse; Berg, Margaret A; Huang, Jingzi (Language and Education, 2018)
Our study focuses on Choice and Evaluation, two of Mohan's knowledge structures to uncover how teachers and students across content areas developed disciplinary knowledge through classroom talk. Participants included in-service teachers and their students in rural and urban secondary schools in the Eastern and Western US. Through Choice and Evaluation, we examined opportunities for students across four disciplines to build up their knowledge of content matter or field. Findings revealed that teachers of math and science built students' field knowledge through classroom exploration, eliciting Evaluation in dialogic patterns involving Choice, while social studies and language arts teachers helped students implicitly use Choice/Evaluation through projects based on their previous experiences. The essential role of student background knowledge in enabling participation across different types of oral exchanges is shown. This study uncovers tendencies across classrooms and makes linguistically informed suggestions for teachers in the disciplines.
0 citations (Crossref) [2023-10-31] Citation Key Alias: gleasonPatternsOralChoice2018, lens.org/109-314-805-638-437 tex.type: [object Object]
Keywords: Teacher education; classroom discourse; dept.wll; language across content; peer-reviewed

Inclusive pedagogy for English language learners: A handbook of research-informed practices - Verplaetse, Lorrie Stoops; Migliacci, Naomi (Routledge, 2017)
In this Handbook leading researchers, teacher educators, and expert practitioners speak to current and future educators and educational leaders in understandable language about the research that informs best practices for English language learners integrated into the K-12 public school system. Responding to current state and federal mandates that require educators to link their practices to sound research results, it is designed to help educators to define, select, and defend realistic educational practices that include and serve well their English language learning student populations. A critical and distinctive feature of this volume is its non-technical language that is accessible to general educators who have not been trained in the fields of second-language development and applied linguistics. Each chapter begins with a thorough discussion of the recommended practices, followed by a description of the research that supports these practices. The rigor of reported research is contained, but this research is written in a lay person’s terminology, accompanied by bibliographies for readers who wish to read about the research in technical detail. The volume is structured around four themes:• In the Elementary Classroom• In the Middle and Secondary Classroom• School and Community Collaboration• School and District Reform. Inclusive Pedagogy for English Language Learners is intended for current and future educational administrators, all educators who have a keen interest in school reform at the classroom, school, or district level, and staff developers, policy makers, parents and community groups, and anyone interested in the successful education of linguistically and culturally diverse students.
Keywords: dept.wll

Soldier-poet or écrivain-combattant: How the French trenches of World War I defined witnessing - Gleisner, Nichole T. (Studies in 20th & 21st Century Literature, 2017)
0 citations (Crossref) [2023-10-31]
Keywords: dept.wll

Patterns of tasks, patterns of talk: L2 literacy building in university Spanish classes - Gleason, Jesse; Slater, Tammy (Language, Culture and Curriculum, 2017)
Second language (L2) classroom research has sought to shed light on the processes and practices that develop L2 learners' abilities [Nunan, D. 2004. Task-based language teaching. London: Continuum; Verplaetse, L. 2014. Using big questions to apprentice students into language-rich classroom practices. TESOL Quarterly, 179, 632-641; Zeungler, J., & Mori, J. 2002. Microanalyses of classroom discourse: A critical consideration of method. Applied Linguistics, 23(3), 283-288]. Honing in on the micro-level of classroom tasks and even further into the language of the tasks can help to reveal the patterns in teacher- and student-talk that help scaffold students' academic literacy. Literacy, from a systemic functional view of language learning, entails having the tools to function in the social contexts that are valued in students' lives. This study illustrates how grounded ethnography was used in conjunction with functional discourse analysis to illuminate bi-literacy development in two third-year university Spanish writing classes. Findings uncovered unique patterns of tasks and oral interactions that helped build students' academic bi-literacy. While grammar tasks helped build students' knowledge of wording-meaning relationships, culture and writing tasks supported their evolving understanding of how language construes content. This study puts forth a systemic functional curricular model for literacy-based tasks that aims to bridge the previously observed language-content gap.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/037-343-356-989-268, pop00144 tex.type: [object Object]
Keywords: Language learning tasks; academic literacy; blended learning; classroom discourse; dept.wll; systemic functional linguistics; third-year Spanish courses

Ghost returns and historical memories in Zhang Yimou's Gui lai and Pedro Almodóvar's Volver - Weng, Miaowei (Canadian Review of Comparative Literature / Revue Canadienne de Littérature Comparée, 2017)
0 citations (Crossref) [2023-10-31]
Keywords: dept.wll